ANALISIS YURIDIS KONFLIK KOMPETENSI PENYELESAIAN SENGKETA PEMBERHENTIAN DIREKSI MELALUI PENGADILAN NEGERI DALAM PERSPEKTIF KEPASTIAN HUKUM - Anna Khoirunisya; Efridani Lubis; Achmad Jaka Santos Adiwijaya (JURNAL ILMIAH LIVING LAW, 2022)
The aims of this study are: 1) To compare the results between district court decisions and industrial relations comparisons in disputes regarding the dismissal of company directors in the perspective of legal certainty, and 2) proposals issued for the settlement of the dispute. The method used in this research is a normative juridical approach or library research. The results of this study found that the dismissal of directors that occurred was purely a civil dispute whose authority was in the district court so that there was an error from the district court judge in applying the normative provisions of the limited liability company law and labor law related to the position of company directors. The Board of Directors is a company organ appointed by the GMS and is authorized and fully responsible for managing the company. The legal relationship between the board of directors and the shareholders is a fiduciary duties and the provision of a mandate (legal mandatory), not a working relationship between workers and employers. So the dispute on the dismissal of the company's directors is an ordinary civil dispute that must be resolved in the District Court